An experimental test of crocodilian stick-displaying behavior. Issue 3 (3rd May 2020) - Rosenblatt, Adam E.; Johnson, Alyssa
Abstract : Tool use has been documented across a diverse array of animals; however, this behavior has received little attention in reptiles. Recently, researchers reported observations of two crocodilian species apparently using sticks as lures to aid in the capture of nesting birds, but the evidence for the behavior was anecdotal and correlative. To explore the behavior in a more controlled situation we designed an experiment to explicitly test the ability of crocodilians to tailor stick-displaying behaviors to specific environmental contexts using four captive pond-dwelling American alligator ( Alligator mississippiensis ) populations, two of which reside near bird rookeries and two of which do not. During bird nesting season we added sticks to each pond and observed the frequency with which each population exhibited stick-displaying behaviors. We found that in most comparisons the frequency of stick-displaying behavior did not differ between rookery and no-rookery sites, while in one comparison the alligators at a no-rookery site actually displayed the behavior more frequently than a paired rookery site. Our results do not generally support the hypothesis that crocodilians tailor stick-displaying behaviors to specific environmental contexts, therefore the hypothesis that crocodilians are true tool users is also called into question. Furthermore, our results suggest that experiments on captive populations are not the ideal way to study stick-displaying behavior because of issues like unrealistic alligator densities and food provisioning.